2020
DOI: 10.24275/rmiq/bio1869
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of autochthonous microorganisms to formulate a defined inoculum for small-scale cocoa fermentation

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…lactis and Limnosilactobacillus fermentum showed strong probiotic potential. Lactococcus lactis has been previously identified in cocoa fermentation processes in Ghana ( Camu et al, 2007 , 2008 ), the Eastern Region of Ghana ( Ayertey et al, 2017 ), and in Aldama, Tabasco, Mexico ( Huerta-Conde et al, 2021 ). Predominantly, during the intermediate and late stages of cocoa fermentation, the prevailing strictly heterofermentative LAB species have primarily been recognized as Limosilactobacillus fermentum (formerly known as Lactobacillus fermentum ) was well documented in prior research ( Camu et al, 2007 , 2008 ; Nielsen et al, 2007 ; Kostinek et al, 2008 ; Lefeber et al, 2011 ; Illeghems et al, 2012 , 2015 ; Moreira et al, 2013 , 2017 ; Papalexandratou et al, 2013 , 2019 ; Pereira et al, 2013a , b ; Ho et al, 2014 ; Ramos et al, 2014 ; Hamdouche et al, 2015 , 2019 ; Batista et al, 2016 ; Bortolini et al, 2016 ; Miescher Schwenninger et al, 2016 ; Visintin et al, 2016 ; Miguel et al, 2017 ; Bastos et al, 2018 ; Mota-Gutierrez et al, 2018 ; Oliveira et al, 2018 ; Romanens et al, 2018 ; Agyirifo et al, 2019 ; Lee et al, 2019 ; Ruggirello et al, 2019 ; Chagas Junior et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…lactis and Limnosilactobacillus fermentum showed strong probiotic potential. Lactococcus lactis has been previously identified in cocoa fermentation processes in Ghana ( Camu et al, 2007 , 2008 ), the Eastern Region of Ghana ( Ayertey et al, 2017 ), and in Aldama, Tabasco, Mexico ( Huerta-Conde et al, 2021 ). Predominantly, during the intermediate and late stages of cocoa fermentation, the prevailing strictly heterofermentative LAB species have primarily been recognized as Limosilactobacillus fermentum (formerly known as Lactobacillus fermentum ) was well documented in prior research ( Camu et al, 2007 , 2008 ; Nielsen et al, 2007 ; Kostinek et al, 2008 ; Lefeber et al, 2011 ; Illeghems et al, 2012 , 2015 ; Moreira et al, 2013 , 2017 ; Papalexandratou et al, 2013 , 2019 ; Pereira et al, 2013a , b ; Ho et al, 2014 ; Ramos et al, 2014 ; Hamdouche et al, 2015 , 2019 ; Batista et al, 2016 ; Bortolini et al, 2016 ; Miescher Schwenninger et al, 2016 ; Visintin et al, 2016 ; Miguel et al, 2017 ; Bastos et al, 2018 ; Mota-Gutierrez et al, 2018 ; Oliveira et al, 2018 ; Romanens et al, 2018 ; Agyirifo et al, 2019 ; Lee et al, 2019 ; Ruggirello et al, 2019 ; Chagas Junior et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the pods have been opened, the most critical step begins, the fermentation. During fermentation, various autochthonous microorganisms deriving from the environment (tools, worker's hands), pod surfaces, and fermentation containers utilize the pulp for growth [4,21]. This process is conducted by yeast, lactic acid bacteria (LAB), and acetic acid bacteria (AAB) [22], and is performed in heaps, baskets, trays, or wooden boxes [21].…”
Section: Cocoa Bean Postharvest Stagesmentioning
confidence: 99%
“…During fermentation, various autochthonous microorganisms deriving from the environment (tools, worker's hands), pod surfaces, and fermentation containers utilize the pulp for growth [4,21]. This process is conducted by yeast, lactic acid bacteria (LAB), and acetic acid bacteria (AAB) [22], and is performed in heaps, baskets, trays, or wooden boxes [21]. However, wooden boxes are most commonly used for the fermentation of cocoa beans worldwide [4].…”
Section: Cocoa Bean Postharvest Stagesmentioning
confidence: 99%
“…Several authors have found that good quality in fermented dry cocoa beans was correlated with good on-farm agricultural and post-harvest practices, bean selection, placenta removal prior to fermentation, and blending of the cocoa bean pulp mass. During the fermentation, there is a well-defined microbial succession of yeasts, lactic acid bacteria (LAB), and acetic acid bacteria (AAB) [5], however, filamentous fungi can also grow, mainly in the well-aerated and cold outer layers of the fermentation mass and during the drying process [6,7]. Contamination with filamentous fungi has been associated with internal development of mould, off-flavours, increased free fatty acid levels, and the production of mycotoxins [8].…”
Section: Introductionmentioning
confidence: 99%